Nos bastidores da igreja : reflexos do declínio da influência da teologia da libertação nas pastorais da arquidiocese de Curitiba (1981-1992). - Westphal, Ezequiel (2008)
The Theology of Liberation develops its basis on a social and economic context of injustice and puts aside the social minorities. This status assumption in favor of the poor became known as “preferential option for the poor” and not only asigns the latin-american theology , but also identifies the Third World Church in a focus and place change, from which makes significant the systematization and the analytic understanding of its history. It will be given emphasis to the reflection concerning to the “power” category, in order to analyse the environment where occurs the shock among the social actors arround the interests in the relationships of the social field. The retaliations imposed to the Theology of Liberation and the political and economic changes, occurred in the last quart of the last century, cause paradigms crisis, not only in the political sphere but also in the theologic one. But the considerations concerning to the Archdiocese of Curitiba privilege the reflections about the questions of the national conjuncture and of the crisis in the institutional relationships that envolved historically the State and The Brazilian Church, relating them, at a local level, in the constitution of the diocese rule. The relationships of ecclesiastic power are analysed through the actions of the bishops, envolving local tensions as the formation of the cleric and the representation of the episcopal authority. The pastoral organization of the Archdiocese of Curitiba in the years 80’ and the beginning of the 1990 decade reflects the ecclesiastic power conjuncture concerning to the types, focus and the dynamics of the pastorals of the archdiocese, particularly the CEB’s and their relationships with the Theology of Liberation. It is necessary to look for decline reasons of the Theology of Liberation influence in the pastoral orientations of the Archdiocese of Curitiba, through quantitative research technics in the study of São Pedro Apóstolo (Saint Peter Apostle) Parish case in Curitiba, in order to analyse the complex relationships of power in the rupture of the speech unit and of the social representations.